The City's Surplus - Architecture + waste - Malan, Maria (School of Architecture, Planning and Geomatics, 2023)
Waste. The stuff we throw away, the spaces we forget about, the buildings that have lost their initial purpose. The wasted human lives that had to make way for something or someone new. Living along with and within waste has become our reality. The way that we deal with it has the potential to impact the future of our planet and of the beings that inhabit it. Something which was once of high value has become surplus. This dissertation aims to flesh out the ideas of the surplus in order to expose its layers on an urban, architectural, material and human scale and the opportunities it holds within a cityscape. The exploration of the surplus is approached through using methods of collage, unpacking palimpsest, and looking toward the theories of re-urbanism, adaptive reuse and repurposed waste as construction materials as ways of dealing with the surplus on an urban, architectural and material scale. The main method of exploration is a speculative design proposal in order to translate theories into a threedimensional contextual response. The surplus, which is inherent in every layer of the city and this site, enables the proposal to manifest in the form of a mixed-use program (industrial, commercial, tourism, community focussed). A dynamic space that punctures into the wasted scape of the Hout Bay harbour, in the derelict Oceana Fish Meal Plant buildings. An adaptive reuse urban and building project which builds with, into, on and for the surplus – it intends to become both a place for dynamic programs and to become dynamic in itself. The architecture explored in this research looks at simple, durable, almost factory-like construction. The complexity of layers found in the site results in an intervention that is born out of the site in order to ultimately serve it and the surrounding community of Hangberg and Hout Bay since, with the loss of fishing quotas and employment opportunities in the harbour, they have also begun to be regarded as a form of surplus. Through the lens of waste this proposal aims to spark and/or continue the conversation around dealing with waste and the surplus in order to address the importance of changing our relationship with it.